Effect of independent alloying of zirconium with bronze and niobium on superconducting properties of Nb3Sn in a Cu(Sn)/Nb system. (1st July 2023) - Srivastava, Nitin; Santra, Sangeeta
Abstract: The present work focuses on the effect of internal (niobium) and external (bronze) alloying of Zr on the superconducting properties of Nb3 Sn in a Cu(Sn)/Nb system through the diffusion couple method. Alloying of Zr with either Cu(5.5 at.% Sn) or Nb enhances the critical current density (Jc ) of the Nb3 Sn superconductor phase developed at the interdiffusion zone of Cu(5.5 at.% Sn, 2 at.% Zr)/Nb and Cu(5.5 at.% Sn)/Nb(2 at.% Zr). Enhancement of Jc of Zr-alloyed Nb3 Sn has been attributed to an increment in grain boundary fraction for Nb3 Sn. Dew Hughes model provided an insight into the pinning mechanisms responsible for enhancement of Jc . Strengthening of pinning forces of Nb3 Sn with internal alloying of Zr might have originated because of the nanometer-sized β-(Nb, Zr) second-phase developed within the Nb3 Sn phase matrix. No change in critical temperature for Zr-alloyed Nb3 Sn makes Zr a suitable alloying element for applications. Graphical abstract: Image, graphical abstract